Development of biogenic bimetallic Pd/Fe nanoparticle–impregnated aerobic microbial granules with potential for dye removal. (1st September 2021) - Kubendiran, Hemamalathi; Alex, Sruthi Ann; Pulimi, Mrudula; Chandrasekaran, N.; Nancharaiah, Y.V.; Venugopalan, V.P.; Mukherjee, Amitava
Abstract: The objective of this study was to develop bimetallic core–shell Pd/Fe nanoparticles on the surface of aerobic microbial granules (Bio-Pd/Fe) and to evaluate their dye removal potential using a representative dye, methyl orange (MO). The aerobic microbial granules (1.5 ± 0.32 mm) were grown for 70 days in a 3-L glass sequencing batch reactor (SBR) with a 12-h cycle time. The Bio-Pd/Fe formation was catalyzed by the Bio-H2 gas produced by the granules. The developed Bio-Pd/Fe was further used for MO removal from aqueous solutions, and the reaction parameters were optimized by response surface methodology (RSM). The XRD, SEM, EDAX, elemental mapping, and XPS studies confirmed the formation of Bio-Pd/Fe. Under the optimized removal conditions, 99.33% MO could be removed by Bio-Pd/Fe, whereas removal by Bio-Pd, Bio-Fe, aerobic microbial granules, and heat-killed granules were found to be quite low (68.91 ± 0.2%, 76.8 ± 0.3%, 19.8 ± 0.6%, and 6.59 ± 0.2%, respectively). The mechanism of removal was investigated by UV–visible spectroscopy, redox potential analysis, HR-LCMS analyses of the solution phase, and XRD and XPS analyses of the solid sorbent. The degradation products of MO exhibited m/z values corresponding to 292, 212, and 160 m/z. The remnant toxicity of the intermediate degradation products was analysed using freshwater algae, Scenedesmus sp. And Allium cepa, as indicator organisms. These assays suggested that after the treatment with Bio-Pd/Fe, MO was transformed to a lesser toxic form. Graphical abstract: Image 1 Highlights: Bimetallic Pd/Fe NPs formation over the surface of aerobic microbial granules. Increased MO removal by Bio-Pd/Fe than Bio-Pd, Bio-Fe, and microbial granules. Stable, re-useable Bio-Pd/Fe applied for treating real wastewater samples. Toxicity of MO significantly reduced after treatment with Bio-Pd/Fe NPs.